Geoinformatics and Data Mining in Earth Sciences (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
This reprint presents a collection of articles on recent advances in data mining, systems analysis, geoinformatics, Big Data theory and practice, and GIS systems with applications for a wide range of Earth Science disciplines. It brings together state-of-the-art results in scientific areas such as seismic hazard and seismic risk, geodynamics and tectonics, Earth gravity, geoecology, GNSS applications, climate change, radioactive waste disposal, spatial disparities, mining surveys, GIS logistics, and other Earth science disciplines, including interdisciplinary ones.